The language of hermaphrodites as they speak their own special kind of language within their community in Bangladesh - Kaderi, Ahmed Salehin (BRAC University, 2010)
Languages take birth and die out in this world; and there are still languages that we have not yet discovered. With this hypothesis in mind a search shows that the hermaphrodites in Bangladesh speak their own kind of language to communicate within their own community. They call their language the “Reverse Language” and speak it to hide and isolate them from the so called mainstream society. There are many reasons why they speak this language, the origin of the Reverse Language being rooted in Bengali as the native language. But the divergences and convergences are very different in the case of the Reverse Language. This study therefore shows what language the hermaphrodites speak, and how we can hypothesize this language to have its roots in the mother tongue.